Umbilical Endometriosis: A Case Report (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Background: Endometriosis is defined as the presence of the endometrium other than the uterine cavity. It is also considered a chronic inflammatory disease associated with immune processes. 1 This disease was first described by Daniel Shroen in 1690 in the work “Disputatio Inauguralis Medica de Ulceribus Ulceri”. The symptoms of this disease were presented by Arthur Duff in 1769. 2 The ectopic endometrium is functionally similar to the eutopic endometrium. It is a benign, estrogen-dependent, gynecological disease; however, due to the accompanying ailments and chronic nature, it is a very important medical, social and economic problem. This disease affects from 10–15% of women of reproductive age and 35–50% of women with pelvic pain and/or infertility. 3 The vast majority of cases of endometriosis occur in women between menarche and menopause. The peak of the disease falls in the period between 25 and 45 years of age.2 Endometrial foci outside the uterine cavity may appear, for example, in the peritoneal cavity, ovaries, bladder or ureters.4 Extrapelvic endometriosis occurs less commonly. The extrapelvic sites include the diaphragm, pulmonary, urinary tract, gastrointestinal tract, brain, surgical scar and cutaneous endometriosis. Umbilicus is a physiological scar that is a preferred site for umbilical endometriosis, as described by Yu et al.5 It represents 0.5% to 1% of all cases of extragenital endometriosis.Primary umbilical endometriosis is first described by Villar in 1886; therefore, it is also known as Villar’s nodule and since then more than 100 cases have been described.6,7 The pathogenesis of endometriosis is not well understood. Postulated theories include Sampson’s theory of retrograde menstruation, which is the commonest, coelomic metaplasia, induction theory, embryonic Mullerian rests, bone marrow stem cell theory, and hematogenous/lymphatic spread. The theory favored in the case of umbilical endometriosis is hematogenous/lymphatic spread where there is coexisting pelvic endometriosis. Isolated umbilical endometriosis could develop from metaplasia of urachal remnants 2,7,8,9,10.The aim of this study is to report one such case of umbilical endometriosis because of its rarity as well as the management option we experienced during the management of this patient.Case report: A 38-year-old woman presented with complaint of a swelling at her umbilical region which bleeds spontaneously. She was menstruating for last 3 days without any pain (picture 1). On examination, there was a dark bluish cystic swelling at umbilicus and dried clotted blood around the swelling. It was about 2cm x2cm size like a big black berry (Picture 2). She is married for 16 years, menstruating regularly with average flow and duration. Her husband works abroad and she never practices any contraceptive method. She had two children; one delivered vaginally and another by cesarean section 7 years back. For the last two cycles her menstrual flow was more than average. Her medical history was unremarkable. Her general and abdominal examination findings was unremarkable. Her hemoglobin level is 11.6gm/ dl; serum TSH level was 3.24mic IU/ml. Her day 12 ultrasonogram (USG) of pelvic organ was normal and usg of umbilical lesion slowed a solid area and measured 0.4 cm x0.4 cm. Our clinical diagnosis was umbilical endometriosis. Patient was offered both medical and surgical management and she opted to have oral contraceptive pill and Naproxen Sodium 500mg immediately. She again menstruates after 28 days; no umbilical bleeding and umbilical swelling was shrunken. (Picture 3). She was followed regularly and counseled to continue OCP and Naproxen 500mg during menstrual period to reduce menstrual flow and recurrence of umbilical swelling. (Picture 4, 5, 6)Discussion and conclusion: Umbilical endometriosis is the commonest type of cutaneous endometriosis. Some case reports have also described the presence of umbilical endometriosis during pregnancy. 7,11 The risk of developing endometriosis is the lowest in black women, the highest in Asian women. Caucasian women have a higher risk of getting sick than black women.12Bangladesh J Obstet Gynaecol, 2024; Vol. 39(1): 49-52